Potential mechanisms for osteopathic manipulative treatment to alleviate migraine-like pain in female rats - Byrd, Katherine; Lund, Makayla; Pan, Yan; Chung, Brandon H.; Child, Kaitlyn; Fowler, Danny; Burns-Martin, Jared; Sanikommu, Mythili; Henderson, Hallie; Gregory, Caroline; Fleming, Regina K.; Xie, Jennifer Yanhua (Frontiers in Pain Research, 2024)
Introduction Migraines are the leading cause of disability in the United States, and the use of non-pharmaceutical treatments like osteopathic manipulative treatment (OMT) has shown promise. Despite its potential, the lack of mechanistic understanding has hindered widespread adoption. This study aims to investigate the efficacy of OMT in treating acute migraines and unravel its underlying mechanisms of action. Methods Female rats were subjected to a “two-hit” approach to induce migraine-like pain. This involved bilateral injections of Complete Freund's Adjuvant (CFA) into the trapezius muscle (1st hit) followed by exposure to Umbellulone, a human migraine trigger, on Day 6 post-CFA (2nd hit). Soft tissue and articulatory techniques were applied to the cervical region for acute abortive or repeated prophylactic treatment. Cutaneous allodynia and trigeminal system activation were assessed through behavioral tests and immunohistochemical staining. Results Following Umbellulone inhalation, CFA-primed rats exhibited periorbital and hind paw allodynia. Immediate application of OMT after Umbellulone inhalation as an abortive treatment partially alleviated cutaneous allodynia. With OMT applied thrice as a prophylactic measure, complete suppression of tactile hypersensitivity was observed. Prophylactic OMT also prevented the increase of c-fos signals in the trigeminal nucleus caudalis and the elevation of calcitonin gene-related peptide expression in trigeminal ganglia induced by CFA and Umbellulone exposure at 2 h post-inhalation. Discussion These findings provide mechanistic insights into OMT's migraine-relief potential and underscore its viability as a non-pharmacological avenue for managing migraines.